Management of sheath blight of rice through essential oils, aroma compounds and plant extracts - RAJENDRA KUMAR and DHIRAJ SINGH, JANKI KANDHARI*, C. DEVAKUMAR (Indian Phytopathology, 2010)
Efficacy of thirteen essential oils and nine aroma compounds were tested against sheath blight ( Rhizoctonia solani) of rice on a susceptible variety Pusa Basmati-1 by spraying on the plants in pot culture. All the essential oils and aroma compounds were found effective against sheath blight. Among essential oils, winter green and eugenol (constituent of clove oil) showed maximum disease reduction of 82.3% and 70.7%, respectively by spraying on the plants. Considering the higher volatability of the essential oils, root dipping of seedlings prior to transplantation was done for eight essential oils, five aroma compounds and four plant extracts in the field. All the essential oils, aroma compounds and plant extracts tested, were found effective against sheath blight. Clove oil (essential oil), ïƒ¡-terpinyl acetate (aroma compound) and Piper betle (plant extract) showed maximum disease reduction of 43.7%, 41.3% and 44.4%, respectively. However, carbendazim 50 WP (check), showed highest disease reduction of 84.4%.